2019
DOI: 10.1111/hepr.13404
|View full text |Cite
|
Sign up to set email alerts
|

Augmenter of liver regeneration enhances cell proliferation through the microRNA‐26a/Akt/cyclin D1 pathway in hepatic cells

Abstract: Aim Hepatocytes can proliferate and regenerate when injured by toxins, viral infections, and so on. Augmenter of liver regeneration (ALR) is a key regulator of liver regeneration, but the mechanism is unknown. The role of ALR in other cell types is not known. In the present study, we investigated the relationship between microRNA (miRNA)‐26a and ALR in the Huh7 cell line and adipose tissue‐derived mesenchymal cells from chronic liver disease patients and healthy individuals. Methods Huh7 cells were transfected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Recent studies have highlighted that immune regulation is another unique biological role of ALR. Gupta et al assumed that a possible mechanism for ALR in liver regeneration is to inhibit certain activities of the organ's inherent natural killer cells [ 30 , 31 ]. We found that exogenous ALR inhibits the activation of NF- κ B by downregulating the expression of TLR4 protein and mRNA, thereby inhibiting the inflammatory response of NRK-52E cells induced through hypoxia and reoxygenation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted that immune regulation is another unique biological role of ALR. Gupta et al assumed that a possible mechanism for ALR in liver regeneration is to inhibit certain activities of the organ's inherent natural killer cells [ 30 , 31 ]. We found that exogenous ALR inhibits the activation of NF- κ B by downregulating the expression of TLR4 protein and mRNA, thereby inhibiting the inflammatory response of NRK-52E cells induced through hypoxia and reoxygenation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent reports demonstrated that numerous signaling pathways are involved in this process and their interactions are complex. Gupta et al (2019) found that ALR (augmenter of liver regeneration, a protein that was identified to specifically support liver regeneration) induced miRNA-26a expression, upregulated the p-Akt/cyclin D1 pathway, and promoted hepatic cell proliferation. Lai et al (2015) found that EGR-1 (early growth response 1 gene)-induced GGPPS plays an important role in post-PH liver regeneration via RAS/MAPK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of ALR inhibited the proliferation and triggered the apoptosis of U266 human multiple myeloma cells ( Zeng et al, 2017 ). Conversely, ALR overexpression in hepatic cells enhanced cell proliferation via the microRNA-26a/p-Akt/cyclin D1 pathway ( Gupta et al, 2019a ).…”
Section: Genetic Factors In Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%